How much do we know about the impact of the economic downturn on the employment of migrants? - Xin Meng; Sherry Tao Kong; Dandan Zhang (Asian Development Bank Institute (ADBI), 2010)
The employment shock of late 2008 in the People's Republic of China (PRC) may have been a product of three different events: (i) the contractionary macroeconomic policies introduced by the government and the central bank in 2007 to slow growth, (ii) the introduction of the new Labor Contract Law at the start of 2008, and (iii) the reduction in export orders due to the global financial crisis from the second half of 2008. These three events occurred sequentially, and their impact on employment has been borne most heavily by rural-urban migrants. Using unique data that track 5,000 migrant households in 15 cities from 2008 to 2009, this paper documents the size of the employment impact of the economic downturn, investigates the geographic location and industry distribution of the effect, and examines the types of migrant workers who lost their jobs in 2008 because of the economic downturn. We find that job loss is not confined to export manufacturing industries, nor is it restricted to coastal cities where export industries are located. We interpret this widespread job loss to indicate that the employment shock that took place in the PRC at the end of 2008 and early 2009 was a response to both the global financial crisis and domestic economic policies.
Keywords: J64; 330; Konjunktur; Beschäftigungseffekt; Städtischer Arbeitsmarkt; China